2012
DOI: 10.1107/s0907444912042400
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a novel glucuronoyl esterase fromMyceliophthora thermophilagives new insights into its role as a potential biocatalyst

Abstract: The increasing demand for the development of efficient biocatalysts is a consequence of their broad industrial applications. Typical difficulties that are encountered during their exploitation in a variety of processes are interconnected with factors such as temperature, pH, product inhibitors etc. To eliminate these, research has been directed towards the identification of new enzymes that would comply with the required standards. To this end, the recently discovered glucuronoyl esterases (GEs) are an enigmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 41 publications
3
67
1
5
Order By: Relevance
“…The twisted ␤-sheet is sandwiched between two layers of ␣-helices with the catalytic triad Ser-His-Glu exposed on the protein surface. A similar 3D structure was reported for GE from Myceliophthora thermophila (earlier assigned as Sporotrichum thermophile) (20) (Fig. 1).…”
Section: Structure and Proposed Mode Of Actionsupporting
confidence: 48%
See 1 more Smart Citation
“…The twisted ␤-sheet is sandwiched between two layers of ␣-helices with the catalytic triad Ser-His-Glu exposed on the protein surface. A similar 3D structure was reported for GE from Myceliophthora thermophila (earlier assigned as Sporotrichum thermophile) (20) (Fig. 1).…”
Section: Structure and Proposed Mode Of Actionsupporting
confidence: 48%
“…A mutation of catalytic serine to alanine in M. thermophila GE abolished the enzyme activity (21) but did not affect its active site architecture (20). The mutant was also successfully crystallized with methyl 4-O-methyl-D-glucopyranuronate, an artificial GE substrate (5), to reveal the topology of the active site (20). In contrast to the majority of serine type esterases, glutamic acid replaces aspartic acid in known GEs.…”
Section: Structure and Proposed Mode Of Actionmentioning
confidence: 99%
“…These sequences are strongly conserved in all GE sequences, suggesting again the importance of these residues as the components of catalytic triad. In support of our proposal, the crystal structures of Cip2 and StGE (Charavgi et al, 2013;Pokkuluri et al, 2011) showed that the disulfide bond is formed between the cysteine residues equivalent to Cys304 and Cys440 in NcGE that links the consensus sequences VTGCSRXGKGA and HC, hence bringing serine and histidine residues close together in the catalytic site (Charavgi et al, 2013;Katsimpouras et al, 2014). Cys336 involved in another disulfide bond with Cys412 is near E328 and both of these residues are also highly conserved, possibly assisting in introducing glutamic acid to create the catalytic triad.…”
Section: Discussionmentioning
confidence: 63%
“…From the alignment of homologous sequences, a novel consensus sequence G-C-S-R-X-G conserved in CE15 family members was suggested (Topakas et al, 2010). This consensus was further supported by the crystal structures of two glucuronoyl esterases, Cip2 and StGE2 (Charavgi et al, 2013;Pokkuluri et al, 2011), which confirmed the presence of this sequence in the catalytic center and the role of central serine residue as a nucleophile in the substrate cleavage. Later, the cloning of ScGE from Schizophyllum commune (Wong et al, 2012) was performed, followed by two other GEs from Podospora anserine and Cerrena unicolor (d 'Errico et al, 2015;Katsimpouras et al, 2014).…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation